(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the category of number in linguistics, examining how languages express quantity through grammatical distinctions. It discusses the basic singular-plural distinction common in many languages, as well as more complex systems, including dual, trial, paucal, and inclusive/exclusive forms. The article highlights the role of number in noun, pronoun, verb, and adjective agreement and explores how some languages use classifiers or measure words for uncountable nouns. The piece also touches on typological variation, showing how different languages approach the concept of number, from the simple systems in English to the more intricate ones in languages like Russian or Māori. The article concludes by emphasizing the diversity of number systems and how these reflect both cognitive and cultural factors in language structure.